2023
DOI: 10.7759/cureus.38688
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cement Space Parameters on the Marginal Adaptation of Milled Endocrowns: An In Vitro Study

Abstract: Background Cement film space plays a significant role in achieving good adaptation of indirect restorations. The objective of this study is to investigate the effect of cement space parameters on the marginal adaptation of computer-aided design (CAD)/computer-assisted manufacturing (CAM) endocrowns. Methodology The coronal part of 10 freshly extracted human mandibular molars was reduced to a level of 1.5 mm above the cementoenamel junction (CEJ); then, root canal treatment was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…All included studies were in vitro studies [ 12 28 ]. The highest number of publications, 7 studies (41%), was from the year 2023 [ 12 15 , 19 , 20 , 22 ], followed by years between 2020 and 2022, with 6 studies (35%) [ 20 , 21 , 25 28 ]. Fourteen (76%) studies reported using natural teeth [ 12 15 , 17 23 , 25 27 ], 12 studies (71%) were for mandibular arches [ 13 17 , 19 – 20 , 22 25 , 27 ], and 11 studies (65%) were for molars [ 13 16 , 19 , 22 25 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All included studies were in vitro studies [ 12 28 ]. The highest number of publications, 7 studies (41%), was from the year 2023 [ 12 15 , 19 , 20 , 22 ], followed by years between 2020 and 2022, with 6 studies (35%) [ 20 , 21 , 25 28 ]. Fourteen (76%) studies reported using natural teeth [ 12 15 , 17 23 , 25 27 ], 12 studies (71%) were for mandibular arches [ 13 17 , 19 – 20 , 22 25 , 27 ], and 11 studies (65%) were for molars [ 13 16 , 19 , 22 25 , 27 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The highest number of publications, 7 studies (41%), was from the year 2023 [ 12 15 , 19 , 20 , 22 ], followed by years between 2020 and 2022, with 6 studies (35%) [ 20 , 21 , 25 28 ]. Fourteen (76%) studies reported using natural teeth [ 12 15 , 17 23 , 25 27 ], 12 studies (71%) were for mandibular arches [ 13 17 , 19 – 20 , 22 25 , 27 ], and 11 studies (65%) were for molars [ 13 16 , 19 , 22 25 , 27 , 28 ]. LDGC and zirconia were the most common all-ceramic materials used for endocrown constructions, with 35% and 30%, respectively, and either alone or in comparisons with other all-ceramic materials.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations